Loss of Nigral Hyperintensity on 3 Tesla MRI of Parkinsonism: Comparison With (123) I-FP-CIT SPECT - Bae, Yun Jung; Kim, Jong-Min; Kim, Eunhee; Lee, Kyung Mi; Kang, Seo Young; Park, Hyun Soo; Kim, Kyeong Joon; Kim, Young Eun; Oh, Eung Seok; Yun, Ji Young; Kim, Ji Seon; Jeong, Hye-Jin; et al. (Movement disorders, 2016)
The aim of this study was to investigate whether 3 Tesla susceptibility-weighted imaging can detect the alteration of substantia nigra hyperintensity in Parkinson's disease (PD), multiple system atrophy (MSA), and progressive supranuclear palsy (PSP) and to assess the concordance between the loss of nigral hyperintensity on 3 Tesla susceptibility-weighted imaging and the nigrostriatal dopaminergic degeneration indicated by (123) I-2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl)-nortropane single photon emission computerized tomography. Consecutive subjects with suspected parkinsonism were included, and clinical diagnosis was solidified during clinical follow-up. Two blinded neuroradiologists interpreted the nigral hyperintensity on susceptibility-weighted imaging. The performance of susceptibility-weighted imaging for detection of nigral hyperintensity loss was estimated on the basis of the clinical diagnosis and compared with single photon emission computerized tomography results. The study included 210 subjects (126 PD, 11 MSA, 11 PSP patients, 26 healthy controls, 36 disease controls). The presence or absence of nigral hyperintensity was accurately visualized in 112 PD, 7 MSA, and 11 PSP patients and 53 controls. We identified 16 false-negative cases and 11 false-positive cases. The sensitivity and specificity of susceptibility-weighted imaging were 88.8% and 83.6%, respectively. The concordance rate between susceptibility-weighted imaging and single photon emission computerized tomography was 86.2%. The loss of nigral hyperintensity on susceptibility-weighted imaging suggested nigrostriatal dopaminergic degeneration in a large portion of patients with parkinsonism, which was indicated by (123) I-2β-carbomethoxy-3β-(4-iodophenyl)-N-(3-fluoropropyl)-nortropane single photon emission computerized tomography. In consideration of false-negative and -positive cases, well-designed imaging protocols should be introduced to improve the performance of nigral hyperintensity imaging. © 2016 International Parkinson and Movement Disorder Society.